A Contrastive Study of the Grammaticalization Between “Gan Jing” and “Clean” Based on Corpus - Mengjie Cheng; Hongguo Zhang (Journal of Linguistics and Communication Studies, 2024)
Based on corpus study, this paper makes a diachronic study of the grammaticalization process of the Chinese word “Gan Jing” and English word “clean”. The study shows that both “Gan Jing” and “clean” gradually lose their original meaning and change from a content word to a functional word. The mechanisms of the grammaticalization include reanalysis, analogy, semantic bleaching, metonymy and metaphor, as well as subjectivity. These changes can be attributed to the principle of economy. Though “Gan Jing” and “clean” share many similarities in grammaticalization path, mechanisms and motivations, the use frequency of them varies. The lowly grammaticalized form of “Gan Jing” is most used while the highly-intensified meaning of “clean” is used more widely.